Trends in European political (dis)integration. An analysis of postfunctionalist and other explanations. Issue 8 (3rd August 2019) - Webber, Douglas
ABSTRACT: The divergent outcomes in respect of political integration of the several crises that the EU has confronted during the last decade present a challenge for most 'grand theories' of European integration. There has been more political disintegration than some of the historically most influential, 'optimistic' theories would have anticipated, but less than more recently-developed and more 'pessimistic' theories, notably postfunctionalism, would have expected. Compared with these contrasting theories, a hegemonic-stability-theoretical approach to the EU's crises provides a more convincing explanation of recent patterns of political integration and disintegration.